Purification of peroxidase from Prickly lettuce (Lactuca serriola L.) (Journal of the College of Basic Education, 2022)
Peroxidase was extracted from Prickly lettuce (Lactuca serriola L.) by used sodium phosphate buffer 0.1 M which content 1 mM L-cysteine and 0.1 gm Polyclar AT. crude enzyme was concentrated by gradual addition of ammonium sulfate at 40-80% saturation, the specific activity, fold of purification and yield were 6673 unit/mg, 2.5 and 74.37% respectively. Then purified throw ion exchange chromatography by DEAE-cellulose, the specific activity, fold of purification and yield were 11961 unit/mg, 4.5 and 27.46% respectively, and gel filtration through Sephacryl S-200, the specific activity, fold of purification and yield were 15496 unit/mg, 5.8 and 23.24% respectively.